2018
DOI: 10.1186/s13568-018-0711-3
|View full text |Cite
|
Sign up to set email alerts
|

Expression optimization of recombinant cholesterol oxidase in Escherichia coli and its purification and characterization

Abstract: Cholesterol oxidase is a bacterial flavoenzyme which catalyzes oxidation and isomerization of cholesterol. This enzyme has a great commercial value because of its wide applications in cholesterol analysis of clinical samples, synthesis of steroid-derived drugs, food industries, and potentially insecticidal activity. Accordingly, development of an efficient protocol for overexpression of cholesterol oxidase can be very valuable and beneficial. In this study, expression optimization of cholesterol oxidase from S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 59 publications
0
7
1
Order By: Relevance
“…They found that the maximum cholesterol oxidase production by Streptomyces rimosus was achieved using the optimal levels of process variables which found to be inoculum size (3%, v/v), pH 7, incubation temperature (30°C), incubation time (48 h) and agitation speed (200 rpm). Fazaeli et al [46] achieved maximum cholesterol oxidase production by Escherichia coli when the induced culture production medium was incubated for 24 h at 15°C. Also, Niwas et al [30] studied the effect of process variables on cholesterol oxidase production by Streptomyces sp.…”
Section: Optimization Of the Selected Significant Variables By Box-bementioning
confidence: 99%
“…They found that the maximum cholesterol oxidase production by Streptomyces rimosus was achieved using the optimal levels of process variables which found to be inoculum size (3%, v/v), pH 7, incubation temperature (30°C), incubation time (48 h) and agitation speed (200 rpm). Fazaeli et al [46] achieved maximum cholesterol oxidase production by Escherichia coli when the induced culture production medium was incubated for 24 h at 15°C. Also, Niwas et al [30] studied the effect of process variables on cholesterol oxidase production by Streptomyces sp.…”
Section: Optimization Of the Selected Significant Variables By Box-bementioning
confidence: 99%
“…[44] used a two-step statistical approach to optimize the production of cholesterol oxidase from [46] achieved maximum cholesterol oxidase production by Escherichia coli when the induced culture production medium was incubated for 24 hours at 15°C. Also, Niwas et al [30] studied the effect of process variables on cholesterol oxidase production by Streptomyces sp.…”
Section: Optimization Of the Selected Significant Variables By Box-bementioning
confidence: 99%
“…Typically, the cloning-expression of CHOXs using the heterologous host E. coli, a species Generally Regarded as Safe (GRAS), is considered the gold standard solution for avoiding these obstacles. In this regard, great attention has been paid in recent years toward the cloning and expression of CHOXs from a wide range of pathogenic and non-pathogenic bacteria [2,[26][27][28][29][30][31][32][33], especially after the publication of a plethora of microbial genome sequences by the NCBI.…”
Section: Discussionmentioning
confidence: 99%
“…In general, using high concentrations of sugar as additives in the growth media would lead to a drop in pH below 6.0. This, in turn, would lead to a reduction in cell density [29]. Interestingly, the cell density recombinant protein production profile is diverse with respect to various carbon sources with dissimilar cellular uptake and recombinant protein production in E. coli [43,44].…”
Section: Discussionmentioning
confidence: 99%